Facile synthesis of a mesoporous alumina and its application as a support of Ni-based autothermal reforming catalysts. (9th February 2016) - Sepehri, Soodeh; Rezaei, Mehran; Garbarino, Gabriella; Busca, Guido
Abstract: Mesoporous nanocrystalline γ-Al2 O3 powder with high specific surface area (>220 m 2 /g) was prepared by a "solid state" method and employed as the support for nickel catalysts. Ni catalysts supported on this alumina were prepared and investigated in autothermal reforming of methane. The prepared catalysts were characterized by XRD, BET, DR-UV-Vis, TPR and SEM techniques before and after the reaction. The effect of experimental conditions, such as temperature, space velocity, steam to carbon (S/C) and oxygen to carbon (O/C) ratio was investigated on the catalytic performance of the prepared catalysts. Catalyst with 25 wt.% of Ni content revealed high methane conversion (around 86% at 700 °C). The catalytic activity is reduced by calcination at 800 °C, which results in lower surface area and in the formation of bulk Ni aluminate spinel. Highlights: A simple solid state method was developed for synthesis of mesoporous γ-Al2 O3 . Mesoporous γ-Al2 O3 with high surface area (>220 m 2 /g) was used as catalyst support. Nickel catalyst exhibited high activity and stability in autothermal reforming (ATR). Nickel catalyst showed a low degree of carbon formation in ATR reaction.